CONDIÇÕES E PROJEÇÕES DE ACESSO AO SANEAMENTO BÁSICO NAS CIDADES MÉDIAS BRASILEIRAS - Taís Gonçalves Neto Costa; Carlos Fernando Ferreira Lobo; Weber Soares (Terr@ Plural, 2020)
This paper aims to portray the situation of access to basic sanitation in Brazilian regional capitals as mid-sized cities. It also intends to demonstrate the prospects of access to basic sanitation through projections, considering the advance of demographic growth and the targets set by the Federal Government for a 20-year horizon. Data from the demographic censuses of 1991, 2000, and 2010 were used upon 64 regional capitals. The results show that access to basic sanitation has progressed in recent decades, although serious deficiencies persist, especially due to the country’s regional disparities. The projections highlight a scenario of expansion and, sometimes, the universalization of access, but indicate cases in which the situation should be unsettling, demanding imminent public policies and investments in infrastructure that meet the new local demand